Inclusive participation in information and communication technologies (ICTs) processes for smart services in the city of Johannesburg - Elvin Shava; Shikha Vyas-Doorgapersad (Insights into Regional Development)
Governments everywhere must focus on rethinking service delivery as inclusive involvement in Information and Communication Technologies (ICTs) procedures for smart services has become unavoidable. Metropolitan municipalities in South Africa have joined the technology revolution that embraces smart services delivery through various ICTs and advances the idea of e-governance using the Stakeholder Inclusive Approach. To comprehend how the City of Johannesburg (CoJ) encourages inclusion in smart services, the researchers use an explorative qualitative design that works well with the inclusive stakeholder approach, which supports a collaborative process in ICT adoption. The study discovered through qualitative thematic analysis that inclusiveness is a comprehensive process that considers the demands of different stakeholders in the adoption and implementation of ICT. One issue that leads to ICT efficiencies in the CoJ is data fragmentation from numerous municipal agencies. Inclusionary participation has been widespread in virtual Integrated Development Planning (IDP) forums and other cutting-edge services provided by the CoJ. There have been some exceptional examples of free wifi supply. The study's conclusion reiterates the importance of comprehensive inclusion in ICT adoption and implementation as it links communities with the municipality and stresses the need for city officials to commit to upskilling programmes to improve the delivery of public goods and services delivery.